Pengaruh Citra Merek dan Kualitas Produk Terhadap Keputusan Pembelian Konsumen: Studi Kasus Pada Umkm Kuliner - Mudzakir Ilyas; Rika Rahmadina Putri; Eka Suryani Annisa, Mitha (ADL ISLAMIC ECONOMIC : Jurnal Kajian Ekonomi Islam, 2025)
This study aims to determine the effect of brand image and product quality on consumer purchasing decisions on seblak prabumulih. The method used in this research is quantitative research method using a sample of 100 respondents who have made purchases at seblak prabumulih. The data analysis method used is multiple linear regression analysis to see how much influence brand image and product quality have on consumer purchasing decisions on seblak prabumulih. Based on the results of multiple linear regression analysis that has been carried out in this study, seen from the results of the f test, it can be seen that the Fcount value is 15.246 > Ftabel 3.09 (15.246 > 3.09) then H0 is rejected and H1 is accepted. This means that the Brand Image and Product Quality variables together (simultaneously) have a significant effect on the level of Consumer Purchasing Decisions at the Seblak Prabumulih shop.